2021
DOI: 10.1128/jvi.01714-20
|View full text |Cite
|
Sign up to set email alerts
|

Specific Interaction of NovelFriunavirusPhages Encoding Tailspike Depolymerases with Corresponding Acinetobacter baumannii Capsular Types

Abstract: Acinetobacter baumannii is one of the most clinically important nosocomial pathogens. The World Health Organisation refers it to its «critical priority» category to develop new strategies for effective therapy. This microorganism is capable of producing structurally diverse capsular polysaccharides (CPSs), which serve as primary receptors for A. baumannii bacteriophages carrying polysaccharide-depolymerasing enzymes. In this study, eight novel bacterial viruses that specifically infect A. baumannii strains bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(92 citation statements)
references
References 67 publications
2
89
1
Order By: Relevance
“…It is known that the phage tail fiber or tail spike protein often functions as a polysaccharide depolymerase and targets specific capsule types for enhancing the antivirulence activity [ 41 ]. In A. baumannii , more than 128 types of capsule loci (KL type) have been identified, so even though many phages depolymerase functions have been studied [ 28 , 30 , 37 , 42 , 43 , 44 ], unlike broad-spectrum bactericidal antibiotics, they still target only a limited number of bacterial strains. Therefore, identification of novel depolymerases and evaluation of their ability to control A. baumannii infections is important.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the phage tail fiber or tail spike protein often functions as a polysaccharide depolymerase and targets specific capsule types for enhancing the antivirulence activity [ 41 ]. In A. baumannii , more than 128 types of capsule loci (KL type) have been identified, so even though many phages depolymerase functions have been studied [ 28 , 30 , 37 , 42 , 43 , 44 ], unlike broad-spectrum bactericidal antibiotics, they still target only a limited number of bacterial strains. Therefore, identification of novel depolymerases and evaluation of their ability to control A. baumannii infections is important.…”
Section: Discussionmentioning
confidence: 99%
“…The latent period for TaPaz was about 30 min, and the burst size was approximately 110 particles per infected cell. The host specificity of TaPaz was tested against a collection of A. baumannii strains with biochemically characterized CPS structures belonging to 56 different K types used in our previous study [5] (Table S1). It was found that TaPaz was highly specific as the other depolymerase-carrying A. baumannii phages and was cable to infect only a strain with a certain CPS structure, namely A. baumannii NIPH601 of K47 capsular type.…”
Section: Phage Isolation Morphology Host Specificity and Infection Parametersmentioning
confidence: 99%
“…On the example of several previously characterized A. baumannii phages, it was shown that TSDs encoding in their genomes are responsible for the ability of bacterial viruses to infect the strains with certain CPS structures [5][6][7][8][9][10]12]. Genes encoding two different TSDs that presumably allow TaPaz to infect the representatives of two various Acinetobacter K types were identified in the phage genome.…”
Section: Phage Tapaz Structural Tailspike Depolymerasesmentioning
confidence: 99%
See 2 more Smart Citations